Implementation of Cultural Arts Learning at SMA Negeri 3 Padang - Gevi Sonia, Citra; Hadi, Harisnal (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2023)
This study aims to determine and describe the implementation of cultural arts learning at SMA Negeri 3 Padang. The type of research used in this study is qualitative research with a descriptive approach. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery and mobile phones. Data collection techniques include observation, interviews, literature studies and documentation. The steps in analyzing data are data collection, identifying data, classifying data, clarifying and inferring data. The results showed that the implementation of Cultural Arts learning at SMA Negeri 3 Padang had been carried out well, but there were several things in its implementation that were not in accordance with the teaching module so that the implementation of learning was still ineffective. In terms of the learning method used, the teacher has used a learning method that is in accordance with the material. However, when the teacher practiced the example of singing a popular Indonesian song, namely Anji's song entitled "Menunggu Kamu", the teacher did not use musical instruments such as guitars or keyboards as accompaniment because the teacher was less able to play musical instruments. In learning, students are very excited to participate in learning to sing popular songs in Indonesian or popular songs in foreign languages even though students are still embarrassed to appear singing in front of the class.